Dietary Recommendations for the Management of Non-alcoholic Fatty Liver Disease (NAFLD): A Nutritional Geometry Perspective - Romero-Gómez, Manuel; Aller, Rocío; Martín-Bermudo, Franz (Seminars in Liver Disease, 2022)
Diet could be both culprit and solution of NAFLD. Dietary modifications have been associated with histological features improvement in NAFLD. The Western diet was related to a greater risk of disease progression while the Mediterranean diet (MD) could promote regression of histological lesions. Modifications in the nutrient composition seems to have lesser impact on NAFLD than dietary modifications. An intrinsic interaction between nutrients in the diet support a specific effect not seen when added separately. Dietary modifications should focus on promoting weight loss but also look for patterns that are able to promote histological improvement. Although several micronutrients' deficit has been related to NAFLD progression, prescribing these micronutrients' supplementation did not reach a positive impact. However, an enriching diet with specific nutrients could be useful, like olive oil supplemented in MD. Geometry of nutrition defines a framework to better understand the interaction between nutrients, foods, and dietetic pattern in the model of diseases and how we could approach taking into consideration the interaction between meals and disease features. After analyzing baseline diet and histological lesions, we could calculate the distance to optimal diet and to promote changes in lifestyle to reach all these goals. A standard MD menu would be recommended.
Keywords: dietary recommendations; geometry of nutrition; food intake; Mediterranean diet